Muscle power is associated with higher levels of walking capacity and self-reported gait performance and physical activity in individuals with cerebral palsy - Pontiff, Mattie E.; Batra, Abhinandan; Li, Li; Moreau, Noelle G. (Frontiers in Physiology, 2025)
IntroductionThe purpose of this study was to investigate the relationships between a Power Leg Press test (PLP) with walking capacity and self-reported performance and participation in individuals with Cerebral Palsy (CP), and to compare the strength of the associations between two power tests (PLP and isokinetic (IsoK)) with walking capacity.MethodsAmbulatory individuals with CP (n = 33; age 17.89 ± 7.52 years) performed five inclined power leg presses at 40%–50% of their 1-repetition maximum “as fast as possible”. A linear position transducer was attached to the weight bar, and the displacement, total load, and angle of the sled were used to calculate peak power for each trial. Isokinetic knee extensor power was measured at 60 deg/sec. Walking capacity was measured using the 10-m walk test fast (FS) and self-selected (SS) speeds and the 1-min walk test (1MWT). Self-reported performance and participation measures were the Activities Scale for Kids-performance (ASKp), Patient-Reported Outcomes Measurement Information System (PROMIS®), and the Gait Outcomes Assessment List (GOAL). Pearson’s correlation coefficients determined relationships between power measures with walking capacity and self-report measures (α < 0.05).ResultsPLP and IsoK power were significantly correlated to SS (r = 0.361, r = 0.376), FS (r = 0.511, r = 0.485), and 1MWT (r = 0.583. r = 0.443), respectively (p < 0.05). There was no significant difference between the strength of the associations between walking capacity and each test of power (PLP and Isok) (p > 0.05). PLP power was significantly correlated to composite scores on the ASKp (r = 0.690) and GOAL (r = 0.577) and to four components of the PROMIS, including physical function (r = 0.588) (p < 0.01). The Gait and Mobility subscale of the GOAL (r = 0.705) and the Locomotion (r = 0.636), Transfers (r = 0.547), and Standing (r = 0.521) subscales of the ASKp had strong relationships to peak power produced during the PLP test (p < 0.01).DiscussionPLP power was significantly correlated with walking capacity and self-reported walking performance and mobility-based participation in ambulatory individuals with CP. Higher movement velocities associated with the PLP test may explain the significant associations of power with faster gait speeds. Self-reported mobility performance and physical activity also showed moderate to strong relationships with lower extremity power. Overall, these results suggest a strong link between decreased muscle power generation and walking limitations in individuals with CP.